2005
DOI: 10.4103/0019-5545.46077
|View full text |Cite
|
Sign up to set email alerts
|

Dhat syndrome in relation to demographic characteristics

Abstract: Background:The area of men's sexual health has been poorly understood, particularly with reference to South Asian cultures. The belief that losing semen is detrimental to health is a concept common to both Oriental and Occidental thinking.Aim:To estimate the number of patients with the dhat syndrome consulting different professionals in Lahore and to examine their demographic characteristics.Method:Seventy health professionals of various types were approached and asked to fill in a daily record form for all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 9 publications
3
31
0
Order By: Relevance
“…Were it not for other supportive literature, we could attribute the influence of district to selection bias. However, studies of dhat syndrome in India and South Asia have consistently found high levels among young and unmarried men, especially those from low to medium socio-economic groups and with low to medium levels of education (Bhatia & Malik 1991;Khan 2005 of our Agra sample consisted of single men, almost three times as many as in Tehri, and 58% were 15-25-years old, compared to 29% in Tehri; income levels were low. These especially educational and economic impoverishment and being single are risk factors for mental health problems (Goldberg & Williams 1988;Patel & Kleinman 2003).…”
Section: Discussionmentioning
confidence: 72%
“…Were it not for other supportive literature, we could attribute the influence of district to selection bias. However, studies of dhat syndrome in India and South Asia have consistently found high levels among young and unmarried men, especially those from low to medium socio-economic groups and with low to medium levels of education (Bhatia & Malik 1991;Khan 2005 of our Agra sample consisted of single men, almost three times as many as in Tehri, and 58% were 15-25-years old, compared to 29% in Tehri; income levels were low. These especially educational and economic impoverishment and being single are risk factors for mental health problems (Goldberg & Williams 1988;Patel & Kleinman 2003).…”
Section: Discussionmentioning
confidence: 72%
“…Keeping in mind aims of the study, we reviewed the available literature with respect to the clinical picture, attitude and beliefs, and treatment used for Dhat syndrome. We also reviewed the only available instrument for assessment of Dhat syndrome .…”
Section: Methodsmentioning
confidence: 99%
“…6 Masturbation is held to be responsible for aggravating depressive symptoms. 7 In Buddhist culture Loss of semen, even the smallest is considered as a corrupt offense. Night time emission is likewise found in a slandering view in early Buddhism and it is considered as a hindrance in the way of otherworldly advancement and to achieve nirvana.…”
Section: Introductionmentioning
confidence: 99%
“…Many deluding articles or religious messages still write that masturbation can cause diminishing of semen and diminished quantities of sperms which thus will make a male inept. 7 Faith healers likewise assume a significance in spreading misguided judgments about the impacts of semen misfortune and masturbation. 10 Present study focuses on giving a detailed description of socio demographic variables of patients suffering from this disorder and the various physical symptoms associated with it.…”
Section: Introductionmentioning
confidence: 99%